Comments on the taxonomic status of Cyrtodactylus zebraicus Taylor, 1962 (Squamata: Gekkonidae) from Northern Peninsular Malaysia - Quah, Evan S. H.; Grismer, L. Lee; Syafiq, Muhamad Fatihah; Rujirawan, Attapol; Aowphol, Anchalee; Ahmad, Amirrudin B.; Anuar, M.s. Shahrul (Zootaxa, 2023)
The taxonomic status of Cyrtodactylus zebraicus in Peninsular Malaysia has been plagued with uncertainty over the last three decades owing to a lack of vouchered material. Recent collections confirmed the presence of this species in the northernmost state of Perlis and for the country. An expanded description of the newly collected Peninsular Malaysian specimens as well as the holotype of C. zebraicus is provided along with a comparison with other Cyrtodactylus species in the country. This study adds to the growing number of herpetofaunal species with Indo-Burmese affinities discovered in northern states of the country and the biogeographic importance of this region for the exchange of fauna and flora. The findings also highlight the importance of continued field work along the biogeographic interchange of the Banjaran Nakawan that separates southwestern Thailand from northwestern Peninsular Malaysia and the need to sample and collect voucher specimens that can be deposited in proper scientific collections for current and future research.